Stock Price And Performance Of Indonesian Banking, Case Study For Period Of 2015-2017 - Cornelius Candra Adi Wibowo (NAROTAMA UNIVERSITY, Indonesia, 2019)
The purpose of this study is to analyze the effect of Return On Assets, Return On Equity and Earning Per Share to Price Book Value and stock prices of Banking Companies listed in Indonesia Stock Exchange (IDX) during 2015-2017. This study analyzes ratios of financial statements of banking companies and their impact on stock prices. The population of this research is Banking Companies listed in IDX during 2015-2017. Samples used are as many as 43 Banking companies with census method. The analytical technique used is Partial Least Square. The financial statements used are from the Indonesia Stock Exchange website and tested with the SmartPLS 3.0 application. Result of this study is ROE and EPS have a significant and positive influence on PBV. ROE, EPS and PBV have significant and positive influence on stock price. However DER has no significant effect on PBV and Stock Price.